DETERMINATION OF BIOACTIVE COMPONENTS OF ANNONA MURICATA LEAF BY GC MS ANALYSIS - Priscilla Sweetlin G; Packia Lincy.M (The Bioscan, 2024)
Phytochemicals are the chemicals extracted from plants. These organic chemicals are classified as primary or secondary constituents, depending on their role in plant metabolism. GC-MS method used forthe analysis of the obtained extract can be an interesting tool for testing the amount ofsome active principles in herbs used in various industries. The aimofthisstudy wasto carry out for identification of bioactive compounds from sample by Gas chromatography and Mass spectroscopy (GC-MS). GCMS analysis of ethanolic Annona muricata leaf extract was done by standard protocol using the equipment Perkin-Elmer Gas Chromatography– Mass Spectrometry, while the mass spectra of the compounds found in the extract was matchedwith the National Institute of Standards and Technology (NIST) library. The GC-MS analysis ofAnnona muricata leaf extract showed the presence of compounds. The prevailing compounds are 1,2-Benzenedicarboxylicacid, diethyl ester, Ergosta-5,22-dien-3-ol, acetate, (3á,22E), 6-Hydroxy-4,4,7atrimethyl-5,6,7,7a-tetrahydrobenzofuran-2(4H)-one, 2-[4 - methyl-6-(2 ,6, 6 – trimethylcyclohex -1- enyl)hexa-1,3,5- trienyl]cyclohex – 1 -en -1-carboxaldehyde, Octadecanal, 1,2-Benzenedicarboxylicacid, butyl octyl ester which have wide range of biological activities.